Analisis Bauran Pemasaran Di PT Haruman Multi Artha Dan Pengaruhnya Terhadap Keputusan Pembelian - Karina Amalia Ningtyas; Anas Hidayat (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
The purpose of this study was to analyze the influence of the marketing mix (marketing mix) which includes product, price, distribution and promotion both partially and simultaneously on purchasing decisions. This type of research is quantitative with customer respondents at PT. Haruman Multi Artha totaling 40 respondents were selected using a purposive sampling technique. Data analysis used multiple linear regression analysis with the IBM SPSS Statistics 23 test tool. The results showed that (1) there was a positive and significant effect of the product on the purchasing decision of PT. Haruman Multi Artha, with a p-value of 0.004 <0.05. (2) There is a positive and significant price effect on purchasing decisions of PT. Haruman Multi Artha, with a p-value of 0.041 <0.05. (3) There is a positive and significant effect of the product on purchasing decisions of PT. Haruman Multi Artha, with a p-value of 0.013 <0.05. (4) There is a positive and significant price effect on purchasing decisions of PT. Haruman Multi Artha, with a p-value of 0.042 <0.05. (5) There is a significant influence of the marketing mix which includes product, price, distribution and promotion simultaneously on purchasing decisions of PT. Haruman Multi Artha, with a p-value of 0.000 <0.05.